Intellectual Property Law: Philosophical Foundations, Theoretical Frameworks, and Cross-Pollination - Jankowska, Marlena; Pawełczyk, Mirosław (PRAWO i WIĘŹ, 2024)
This comprehensive study provides an in-depth analysis of the philosophical underpinnings and theoretical frameworks that shape intellectual property (IP) law. It embarks on a scholarly journey that explores various foundational theories, including John Locke’s labour theory, utilitarianism as influenced by Bentham and Mill, Hegelian personality theory, and others. The study examines how these theories have influenced the formation and evolution of intellectual property law, highlighting the complex interplay between individual creativity, societal needs, and cultural expression. It examines the application of these theories in real-world legal scenarios, offering insights into how they inform current IP law and policy. It also explores the intersection of these theories, demonstrating their multifaceted nature and the balanced approach they bring to IP law, addressing issues such as creators’ rights, the public interest, economic incentives, and cultural diversity. This exploration provides a nuanced understanding of IP law as a dynamic field where philosophical, economic, and social considerations converge to shape laws that reflect broader societal values and priorities.